African seed enterprises [ sowing the seeds of food security - Bentley, Jeffery W. [ (Jeffery Westwood)] , 1955-; Guéi, Robert G.; Mele, Paul van (CABI, 2011)
In most developing countries, good quality seed is hard toobtain and farmers struggle to save seed from one year to the next. This title takes a people-centred look at the companies, public agencies and family farms that are taking on this role and maki a difference to food security across Africa